Effect of holding time on the properties of porous ceramics with high-volume polished slag and its pore structure characteristics - Fu, Siyuan; Liu, Rongjin; Wei, Jiazhan; lv, Wenxin; Zhang, Chengqiang; Ouyang, Zijian (Frontiers in Materials, 2023)
Poor utilization of ceramic polishing slag and uneven foaming at high temperatures are some of the crucial problems associated with the formation of porous ceramics. To overcome this, the present study was designed to prepare closed-ended polishing slag porous ceramics by controlling the holding time. Scanning electron microscope, XRD, and X-CT were used to investigate the effects of holding time on the microstructure, pore structure, and phase composition of porous ceramics. The results showed that the holding time had a great influence on the physical properties of the samples, and it provides uniform porosity without significant change in the composition of the material phase of the porous ceramics. Under a holding time of 30 min, volume density reached up to 0.68 g/cm3, while the water absorption and the apparent porosity were 27.33% and 15.49%, respectively. The compressive strength reached 13.07 MPa, and the pore size distribution is mainly between 25 μm and 100 μm, of which the d30 pore diameter accounted for about 28%, the d50 pore diameter accounted for 25%, the d70 pore diameter accounted for 12%, and the d90 pore diameter accounted for 10% of the pore size distribution. In conclusion, the present study clearly shows that the pore structure and properties of porous ceramics can be effectively controlled by controlling the holding time while using a high volume of polishing slag. The feasibility of X-CT for studying the pore distribution inside porous ceramics was verified.